Efficiency of Banks using the Stochastic Frontier Approach: Evidence from India - Shah, Roopam (2013)
This dissertation contributes to the banking efficiency literature by measuring the efficiency of Indian banks for the period 2001-2011. It employs a Stochastic Distance Function Approach and estimates the efficiency scores using three models - The Error Correction Model, with and without Eta, and the Technical Efficiency Effects Model. The results show that the Error Correction Model without Eta and the Technical Efficiency Effects Model, both produced a substantially high mean efficiency score. The Error Correction Model with Eta showed declining efficiency scores over the 11 year period. However, the average efficiency score was higher than that of the Error Correction Model without Eta which did not take into account time varying effects. Additionally, this study also makes an attempt to determine the factors that influence the profitability of Indian banks using the Profitability Model. However, none of the chosen variables had a significant correlation with the profitability.